Modified JSEG algorithm for reducing over-segmentation problems in underwater coral reef images - Mohammad Sameer Aloun; Muhammad Suzuri Hitam; Wan NuralJawahir Hj Wan Yussof; Abdul Aziz K Abdul Hamid; Zainuddin Bachok (Institute of Advanced Engineering and Science, 2019)
The original JSEG algorithm has proved to be very useful and robust in variety of image segmentation case studies.However, when it is applied into the underwater coral reef images, the original JSEG algorithm produces over-segementation problem, thus making this algorithm futile in such a situation. In this paper, an approach to reduce the over-segmentation problem occurred in the underwater coral reef image segmentation is presented. The approach works by replacing the color histogram computation in region merge stage of the original JSEG algorithm with the new computation of color and texture features in the similarity measurement. Based on the perceptual observation results of the test images, the proposed modified JSEG algorithm could automatically segment the regions better than the original JSEG algorithm.